(untitled) (Innovative professional education, 2025)
Based on the analysis of modern methods for developing project-graphic competence in future technology teachers, key aspects have been identified, including graphic skills, the creation of educational materials, and the integration of digital technologies into teaching. Innovative methodological approaches are considered, particularly the use of CAD systems, 3D modeling, multimedia resources, gamification, and project-based learning. The core competencies of a modern technology teacher are defined, and ways to develop them through STEM education, VR/AR technologies, and digital platforms are proposed. The use of digital tools will contribute to the modernization of the educational process and the training of highly qualified educators